Small-Cell Neuroendocrine Carcinoma Originating From the Nasopharynx: Report of a Rare Case - Aguiar, Artur; Jacome, Manuel; Azevedo, Isabel; Monteiro, Eurico; Castro, Vera (Reports of Radiotherapy and Oncology, 2015)
Introduction: Extrapulmonary small-cell carcinoma, neuroendocrine type is uncommon, particularly in the head and neck region. It represents an extremely rare finding when originating from the nasopharynx, and so far only five cases have been reported. Case Presentation: The authors present a case of a female patient with this tumor type, and describe a treatment strategy that combined radiotherapy and chemotherapy. Conclusions: Persistent disease was documented ten months after treatment completion.